Assessment of irrigation water quality - Kirda C. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
World wide extent of saline of water resources is briefly discussed. Sampling techniques and methods of analysis of water samples with reference to irrigation quality assessment are briefly reviewed. A chronological review of irrigation-water quality criteria is presented and its limitations are discussed. it is shown that water quality alone would not suffice to evaluate potential salinity hazard of irrigation water unless consideration is given to crop, soil, climate and existing agronomic and irrigation management practices. Importance of drainage, land preparation crop rotation, specific irrigation methods and management are discussed as regard their influence on salt balance an the plant root zone.
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)